PERSIAN CULTURAL INFLUENCE ON THE EARLY ISLAMIZATION OF SAMUDERA PASAI: A SYSTEMATIC LITERATURE REVIEW - Ahyal Khairi; Nur Saidah (SOSIOEDUKASI, 2026)
ABSTRACT This study aims to systematically examine the influence of Persian culture on the early Islamization of Samudera Pasai by integrating fragmented scholarly perspectives into a coherent analytical framework. Employing a Systematic Literature Review (SLR) guided by PRISMA 2020, this research analyzes 44 selected studies published between 2015 and 2025 from major academic databases. The findings reveal that Persian cultural influence operated through multiple interconnected dimensions, including maritime trade networks, intellectual and manuscript transmission, Sufi spiritual networks, and material culture. Among these, intellectual and Sufi networks played a more transformative role than previously assumed, particularly in shaping epistemological structures and religious consciousness in the Malay world. The study also highlights the role of Samudera Pasai as a nodal hub within transregional Islamic networks, facilitating both the reception and redistribution of Persianate influences. Furthermore, Islamization is identified as a process of localization and hybridization, where external Persian elements were actively reinterpreted by local communities. The novelty of this study lies in its integrative and multidimensional approach, which moves beyond fragmented and single-dimension analyses by combining economic, intellectual, spiritual, and cultural perspectives within a systematic framework. This study contributes to the literature by offering a more comprehensive and network-based understanding of Islamization in Southeast Asia, while also advancing methodological rigor through the application of SLR in historical research.Abstract should be written in English.